PERANCANGAN SISTEM INFORMASI BOOKING SERVICE KENDARAAN DENGAN METODE RAPID APPLICATION DEVELOPMENT - Dani Dani; Emi Sita Eriana (Institut Sains dan Teknologi Nasional, 2022)
ABSTRACT Providing sales, maintenance, repair and car parts services, the management system at Honda Megatama Kapuk, y where the system already uses information management but not yet ada Booking service booking system that uses a web-based application. The web-based application aims to make it easier for customers to book vehicle services. With this application, an appropriate method is needed in designing the information system. The Rapid Application Development (RAD) method was chosen as a rapid design method with 5 steps of business modeling, data modeling, application design, and application deployment, testing. This method of RAD has the advantage of reducingthe overall development time so that it is suitable for the information system needed by the urgent company si. The results of the design of the booking servise application information system which is designed to have a saving time to make it easier for customers are proven by the test results with the System Usability Scale (SUS) method toget a value of 75 which is between the B-C (good-exellent) graphs. It can be concluded that the vehicle service booking application can provide convenience for admins, owners to control system management and customers for vehicle booking services. Keywords: Booking, Vehicle Servise, Method, Rapid Application Development.